2009
DOI: 10.1105/tpc.109.065953
|View full text |Cite
|
Sign up to set email alerts
|

The WD40 Repeat Protein NEDD1 Functions in Microtubule Organization during Cell Division inArabidopsis thaliana 

Abstract: Although cells of flowering plants lack a structurally defined microtubule-organizing center like the centrosome, organization of the spindles and phragmoplasts in mitosis is known to involve the evolutionarily conserved g-tubulin complex. We have investigated the function of Arabidopsis thaliana NEDD1, a WD40 repeat protein related to the animal NEDD1/GCP-WD protein, which interacts with the g-tubulin complex. The NEDD1 protein decorates spindle microtubules (MTs) preferentially toward spindle poles and phrag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 46 publications
5
98
0
Order By: Relevance
“…In animal cells, neural precursor cell expressed developmentally downregulated protein 1 (NEDD1), targets the gamma tubulin ring complex to the centrosome (Fant et al, 2009). In plants, NEDD1 decorates the spindle poles of plant cells (Zeng et al, 2009) and during interphase labels cytoplasmic spots associated with cortical microtubules (Motose et al, 2008). We therefore used it as a potential marker of microtubule nucleation sites.…”
Section: The Emergence Of Cortical Microtubulesmentioning
confidence: 99%
“…In animal cells, neural precursor cell expressed developmentally downregulated protein 1 (NEDD1), targets the gamma tubulin ring complex to the centrosome (Fant et al, 2009). In plants, NEDD1 decorates the spindle poles of plant cells (Zeng et al, 2009) and during interphase labels cytoplasmic spots associated with cortical microtubules (Motose et al, 2008). We therefore used it as a potential marker of microtubule nucleation sites.…”
Section: The Emergence Of Cortical Microtubulesmentioning
confidence: 99%
“…Biochemical isolations have shown that core proteins are assembled into a complex with stoichiometry similar to the g-TURCs from yeast and animals (Nakamura et al, 2010). g-TURC components g-tubulin, GCP2, GCP4, and GCP-WD have been shown to play an essential role in organization of cortical microtubules, the spindle, and phragmoplast arrays in Arabidopsis thaliana (Binarová et al, 2006;Pastuglia et al, 2006;Nakamura and Hashimoto, 2009;Zeng et al, 2009;Kong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Another peripheral protein, conserved across eukaryotes, is NEURAL PRECURSOR CELL EXPRESSED DEVELOPMENTALLY DOWN-REGULATED PRO-TEIN1 (NEDD1), also known as GCP-WD. NEDD1/ GCP-WD localizes g-TuRC within mitotic spindles in human cells (Haren et al, 2006;Lüders et al, 2006) and was shown to be required for normal cell division in plants (Zeng et al, 2009). NEDD1/GCP-WD localizes g-TuRC within interphase arrays in plants, where it increases the ratio of branch to parallel nucleation (Walia et al, 2014).…”
Section: Microtubule Nucleationmentioning
confidence: 99%